The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/pca.586
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for the analysis of sennosides in Cassia angustifolia by high‐performance liquid chromatography

Abstract: A reversed-phase column liquid chromatographic method for the analysis of sennosides A and B present in leaf and pod extracts of Cassia angustifolia has been developed using a Symmetry C18 column and a linear binary gradient profile. The method can be utilised for the quantitative determination of other sennosides as a baseline resolution for most of the constituents was achieved. The method is economical in terms of the time taken and the amount of solvent used (25 mL) for each analysis. The validity of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Many studies have reported the quantitative analysis of SA and SB by isocratic HPLC [2,3], gradient HPLC [4], ion-pair HPLC [5][6][7], and capillary electrophoresis [8,9]. Some of these studies used solid-phase extraction (SPE) to remove the interfering components.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the quantitative analysis of SA and SB by isocratic HPLC [2,3], gradient HPLC [4], ion-pair HPLC [5][6][7], and capillary electrophoresis [8,9]. Some of these studies used solid-phase extraction (SPE) to remove the interfering components.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis for the estimation of sennoside A and B was performed following the protocol modified from Bala et al (2001). The solvent system consisted of solvent A: methanol + water + acetic acid (20:80:0.1) and solvent B: methanol + water + acetic acid (80:20:0.1).…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Other procedures for the detection of sennosides include reversed -phase column liquid chromatography. 33 Metabolites of anthranoid compounds in senna produce discoloration of the urine that can cause false -positive tests for urinary urobilinogen.…”
Section: Diagnostic Testingmentioning
confidence: 99%